Systematic Review: Meta-Synthesis of Implementation of Act No. 18 of 2019 on Pesantren - Mustofa, Idam; Anwar, Saiful; Yusron, Moh. Alwi; Asrori, Asrori (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2024)
The study explores the implementation of Act No. 18 of the Year 2019 on Pesantren which covers the complexity of Pesantren management, mainly related to adaptation to the demands of the modern era, integrating knowledge into the curriculum, and improved management. The objective of the research is to conduct a meta-synthesis of ten studies related to the implementation of the Act on Pesantren, highlighting aspects such as management, human resources, finance, curricula, facilities, and the role of Pesantren in society. The research method uses a qualitative approach in a systematic review with meta-aggregation techniques. Research results show that the Act on Pesantren has a positive impact, including official recognition of Pesantren’s graduates, protection against the uniqueness of interns, and empowering interns in raising the Human Development Index (HDI) in Indonesia. Nevertheless, there are challenges such as ideological debates and variations in the implementation of the Act on Pesantren in various areas, mainly related to concerns about the loss of Pesantren’s independence.